2011
DOI: 10.1007/s11127-011-9846-3
|View full text |Cite
|
Sign up to set email alerts
|

The illicit drug trade, counternarcotics strategies and terrorism

Abstract: Terrorism, Illicit drug trade, Drug prices, Drug cultivation, Drug interdiction, Drug eradication, D74, C23, H56,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 62 publications
2
27
0
1
Order By: Relevance
“…The adoption of these terrorism indicators is consistent with recent literature on the relationship between terrorism and macroeconomic variables Asongu et al, 2015;Asongu & Kodila-Tedika, 2015a). This adoption is also in line with the engaged trade-terrorism literature because some studies have focused only on a few variables, particularly (i) transnational terrorism (De Sousa et al, 2009ab) on the one hand and (ii) on the other hand transnational and domestic terrorism (Piazza, 2011).…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…The adoption of these terrorism indicators is consistent with recent literature on the relationship between terrorism and macroeconomic variables Asongu et al, 2015;Asongu & Kodila-Tedika, 2015a). This adoption is also in line with the engaged trade-terrorism literature because some studies have focused only on a few variables, particularly (i) transnational terrorism (De Sousa et al, 2009ab) on the one hand and (ii) on the other hand transnational and domestic terrorism (Piazza, 2011).…”
Section: Introductionsupporting
confidence: 67%
“…These studies have been primarily focused on illicit trade. (1) Piazza (2011) has assessed the nexus between 'drugs trade' and terrorism to establish that cocaine production, illicit drugs and opiate considerably fuel terrorism activities (domestic and transnational). On the other hand, the eradication of illicit crops and banning of drugs have opposite effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As far as we are aware, this stream of the literature has focused on inter alia: (i) the effect of terrorism on foreign direct investment (FDI) (Abadie and Gardeazabal, 2008), (ii) interconnections between terrorism and innovation (Koh, 2007), (iii) the growth-terrorism nexus, with bidirectional causality (Gries et al, 2011;Shahbaz et al, 2013;Shahzad et al, 2015), causality to terrorism from growth (Piazza, 2006;Choi, 2015), causality from terrorism to growth (Gaibulloev & Sandler, 2008, 2011Öcal & Yildirim, 2010;Meierrieks & Gries, 2013) and (iv) the relevance of foreign aid in mitigating the potentially negative effect of terrorism on development outcomes like external flows (Bandyopadhyay et al, 2014), conditional on initial levels of external flows or corruption-control levels in the domestic countries . The present line of inquiry is closest to the last stream.…”
Section: Introductionmentioning
confidence: 99%
“…These have essentially been focused on the commercialisation of illegal drugs. (1) Piazza (2011) examined the link between the 'drugs trade' and terrorism on the hypothesis that illicit 'drugs trade' fuels terrorism. The author has concluded that 'cocaine production' and illicit drugs are significant drivers of transnational and domestic terrorism.…”
Section: Introductionmentioning
confidence: 99%